Right Amyand’s hernia: bilateral indirect uncomplicated inguinal hernia with appendix as content on right side - Mathew, Sunil; A., Shashirekha C.; N., Nithyashree K.; Ysetty, Vikram; G., Kavitha (International Surgery Journal, 2022)
Amyand’s hernia is a rare finding of the appendix inside an inguinal hernia sac. Most cases are found intra-operatively during inguinal hernia repair. It is extremely rare and occurs in 1 percent of all inguinal hernias with an estimated rate of 0.07-0.13 percent having associated acute appendicitis. A 60 year old male presented to the hospital with chief complaint of swelling in bilateral inguinal region more on the right side since 6 months associated with chronic cough since 1 month and difficulty in passing urine since 6 months. Patient was taken up for elective right side hernioplasty after taking physicians and pulmonologist opinion for fitness for surgery and urologist opinion for grade II prostatomegaly. Intra operatively indirect hernia sac medial to inferior epigastric artery with appendix as content and hydrocele around 15 ml. The contents were reduced back inside the peritoneal cavity and Lichenstein tension free hernioplasty was performed. Amyand’s hernia widely varies in its presentation, can occur at any age and typically presents in men. The surgical management of Amyand’s hernia includes appendectomy with repair of inguinal hernia through inguinal incision. Amyand’s hernia being an unusual presentation, helps the surgeons to be prepared for such circumstances and do appropriate management.